2018
DOI: 10.31142/ijmei/v4i11.01
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Work Environment on Employee Performance Through the Job Satisfaction in Drinking Water Company Pandaan Indonesia

Abstract: The background of this study aims to determine the effect of work environment on employee job satisfaction, the influence of work environment on employee performance, the influence of job satisfaction on employee performance and to determine the indirect effect of work environment on employee performance through job satisfaction at Drinking Water Company in Pandaan on Water Quality Laboratory. This research is included in explanatory research. In accordance with the objectives to be achieved in this study desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
2
7
0
1
Order By: Relevance
“…This study is in line with the findings of previous studies, which found a significant relationship between work environment variables and employee performance (Akbar, 2017;Fatihudin, 2018;Putri et al, 2019;Pratomo & Warokka, 2013;Widodo, 2014). This finding means that every employee has well received the work environment in DPPKUKM to improve their performance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study is in line with the findings of previous studies, which found a significant relationship between work environment variables and employee performance (Akbar, 2017;Fatihudin, 2018;Putri et al, 2019;Pratomo & Warokka, 2013;Widodo, 2014). This finding means that every employee has well received the work environment in DPPKUKM to improve their performance.…”
Section: Discussionsupporting
confidence: 93%
“…Previous research conducted by Akbar (2017), Fatihudin, (2018, Putri et al (2019), and Widodo (2014) found a significant influence of the work environment on employee work performance. According to Putri et al (2019), a good work environment will make employees feel comfortable at work so as to improve their performance.…”
Section: Work Environmentmentioning
confidence: 87%
See 1 more Smart Citation
“…They identified that job environment and delegated authority are the antecedents of quality of service and employee productivity in organizations. The research of Fatihudin and Firmansyah (2018) reveals that a comfortable work environment has a significant positive influence on employee performance.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…Furthermore, the work environment is another essential factor affecting employee performance (Imran et al, 2012). According to Fatihudin (2018), the work environment is everything that surrounds an employee at work and has an impact on the employee.…”
Section: Introductionmentioning
confidence: 99%